SCLERAL IMBRICATION COMBINED WITH PARS PLANA VITRECTOMY WITHOUT INTERNAL LIMITING MEMBRANE PEELING FOR MYOPIC SCHISIS. Issue 10 (October 2016) - Baba, Takayuki; Tanaka, Sumiyoshi; Nizawa, Tomohiro; Oshitari, Toshiyuki; Yamamoto, Shuichi
Abstract : Purpose: We investigated whether scleral imbrication combined with pars plana vitrectomy without internal limiting membrane peeling would be effective in treating eyes with myopic macular schisis. Methods: In this retrospective, interventional case series, 8 eyes of 8 patients with myopic retinoschisis without a macular hole were studied. Scleral imbrication was done with 6-mm-wide mattress sutures placed at the temporal quadrants. Pars plana vitrectomy and removal of the vitreous cortex were performed, but the internal limiting membrane was not removed. The best-corrected visual acuity was measured, and the retinal morphology was determined by spectral-domain optical coherence tomography before and at 6 and 12 months postoperatively. Results: The mean age of the subjects was 67.1 years. The best-corrected visual acuity improved from 0.71 ± 0.25 to 0.36 ± 0.19 logarithm of the minimum angle of resolution units (Snellen equivalent: from 20/100 to 20/50) at 12 months ( P = 0.028). The axial length was shortened from 29.5 ± 1.7 to 28.5 ± 2.5 at 12 months ( P = 0.012). The central foveal thickness decreased from 540 ± 171 μ m to 170 ± 85 μ m at 12 months ( P = 0.012). In the 6 macular-detached eyes, 5 eyes (83%) had a complete resolution. The curvature of posterior eye wall was flatter at 12 months ( P = 0.049). No retinal complications were observed. Conclusion: Scleral imbrication combined with pars plana vitrectomy can be an effective method of treating myopic schisis. Abstract : Supplemental Digital Content is Available in the Text.Scleral imbrication combined with pars plana vitrectomy was successful in treating myopic schisis even without removing the internal limiting membrane. Surgery-induced full-thickness macular hole and retinal atrophy did not develop during the 12 postoperative months.